Attitudes towards sts relationships: a study with natural sciences professors - Sanabria Totaitive, Inés Andrea; Callejas Restrepo, María Mercedes (Universidad Pedagógica y Tecnológica de Colombia, 2012)
This article is a product of a research process carried out in the framework of the Latin American Evaluation Project of Attitudes Relating to Science, Technology and Society (LAEPARSTS). A Science, Technology and Society viewpoint questionnaire (STSVQ) was applied to Universidad Pedagogica y Tecnologica de Colombia professors of Natural Sciences and Environmental Education. Based on its results, it is presented the identification of professors’ attitudes towards the relationships between Science, Technology and Society (STS). This study centers on an educational perspective of scientific and technological literacy processes, the nature of sciences and technology (NST), and the STS’ relationships. The submitted results are useful to plan strategies in order to reduce the negative index obtained in some sentences, questions and categories in specific topics where failures were evidenced.As for very positive attitudes, these could be used as structuring elements in the reconstruction of negative attitudes so as to achieve significant learning.